Prognostic Value of Pretreatment Lymphocyte-to-Monocyte Ratio and Development of a Nomogram in Breast Cancer Patients - Yin, Ying; Zhang, Yong; Li, Li; Zhang, Shaotong; Liu, Ning; Yuan, Shuanghu (Frontiers in Oncology, 2021)
Purpose: The objective of this study was to explore the prognostic significance of pretreatment hematologic parameters in predicting disease-free survival (DFS) of breast cancer patients. Materials and methods: The medical records of 440 breast cancer patients in Shandong Cancer Hospital from 2003 to 2013 were analyzed retrospectively. Through the results of blood routine before treatment, the absolute lymphocyte count (ALC), absolute neutrophil count (ANC), absolute monocyte count (AMC) and absolute platelet count (APC) in peripheral blood were collected. The lymphocyte-to-monocyte ratio(LMR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and neutrophil-to-monocyte ratio (NMR) were calculated. Cox proportional hazard model was used for univariate and multivariate analysis. The DFS was compared using Kaplan-Meier method. The prognostic nomogram of patients with breast cancer was developed. Results: The median DFS for all patients was 64.10 months. Univariate analysis showed that the DFS was associated with surgical approach, TNM stage, molecular subtype, neoadjuvant chemotherapy, radiotherapy and LMR (p<0.05). TNM stage, molecular subtype and LMR were independent prognostic factors of breast cancer in multivariate analysis (p<0.05). According to the Kaplan-Meier survival curve analysis, patients with higher LMR (≥4.85) were associated with longer median DFS (median DFS, 85.83 vs 60.90, p<0.001). The proposed nomogram incorporated LMR, TNM stage, and molecular subtype got a concordance index (c-index) of 0.69 in predicting 5-year DFS. Conclusion: In breast cancer patients, higher LMR was associated with longer median DFS and the nomogram including LMR, TNM stage and molecular subtype could accurately predict the prolonged 5-year DFS of breast cancer patients.